Quality of life assessment of patients with and without venous ulcer - Thalyne Yurí Araújo Farias Dias; Isabelle Katherinne Fernandes Costa; Márjorie Dantas Medeiros Melo; Sandra Maria da Solidade Gomes Simões de Oliveira Torres; Eulália Maria Chaves Maia; Gilson de Vasconcelos Torres (Universidade de São Paulo, 2014)
OBJECTIVES: to compare the quality of life of patients with chronic venous disease with and without ulcer and to identify the most affected aspects.METHOD: cross-sectional study with a sample of 204 patients with chronic venous disease. The quality of life was assessed with the help of the SF-36 questionnaire. To compare the scores between the groups, the Mann-Whitney test was used, considering a statistically significant difference when p<0.05.RESULTS: the quality of life score of patients with ulcer was lower when compared to that of patients without ulcer, in all domains and dimensions of the SF-36, particularly in the domains physical aspect and functional capacity, with very low scores.CONCLUSION: all aspects of quality of life were more compromised in people with ulcers. These findings can contribute towards a better understanding of the effects of chronic venous disease on the quality of life and towards a better orientation of therapeutic interventions in this population.